The Effect of Strengthening Responsible Character Education on Student Learning Achievement Through Civics Learning at SMP Negeri 8 Satap Tondano - Julien Biringan,; Arif Wibowo,; Kalvin Salindeho Andaria,; Merry Lenda Kumajas, (Technium Education and Humanities, 2024)
The problem in this research is how to maintain the mandatory school personality which influences student learning achievement at SMP Negeri 8 Satap Tondano. This researcher hopes to see whether there is an influence of the required character strengthening efforts on student learning achievement. The methodology used in this test is a preliminary strategy with a Fair Benchmark Gathering Plan pretest and posttest. The population in this survey were all students of SMP Negeri 8 Satap Tondano and the investigation test was 20 students (10 students in class VIII and 10 students in class IX) who were randomly selected from the investigation class and the control class. Judging from the results of the assessment using the t-test at the real level α = 0.05, t_count = 9.952 and t_table = 1.734, because t_count > t_table then H_(o) is rejected and H_1 is recognized. Thus, it is hoped that efforts to strengthen the character of commitment can influence student learning achievement. The scientists proposed that this exploration could serve as a reference in exploring ways to further develop careful individual preparation to help further promote student achievement learning.